Individual and combined contributions of age-specific and sex-specific pulse pressure and brachial-ankle pulse wave velocity to the risk of new-onset diabetes mellitus. Issue 1 (21st June 2021) - Wu, Yuntao; Han, Xu; Gao, Jingli; Wang, Yanxiu; Zhu, Chenrui; Huang, Zhe; Xing, Aijun; Chen, Shuohua; Ma, Yihan; Zheng, Mengyi; Liu, Qian; Tian, Yaohua; et al.
Abstract : Introduction: We aimed to investigate the individual and combined effects of age-specific and sex-specific pulse pressure (PP) and brachial-ankle pulse wave velocity (baPWV) on the incidence of new-onset diabetes mellitus. Research design and methods: Participants in the Kailuan study cohort who were ≥20 years old, participated in follow-up assessments and underwent baPWV measurements in 2010–2011, 2012–2013, and 2014–2015 were studied. The participants were allocated to four groups according to their PP and baPWV status, each categorized as high or normal, according to age-specific and sex-specific median values. Cox proportional hazards models were used to explore the individual and combined effects of PP and baPWV on the incidence of diabetes mellitus. Results: There were 18 619 participants who were followed for 4.27±1.91 years. A total of 877 new cases of diabetes were identified, and the incidence density was 11.03/1000 per year. Using the normal PP and normal baPWV group as the reference group, the multivariable-adjusted HRs and 95% CIs for diabetes mellitus in the high PP and high baPWV groups were 1.08 (0.93 to 1.25) and 1.64 (1.41 to 1.90), respectively. Compared with the normal PP/baPWV group, the HR and 95% CI for diabetes in the normal PP/high baPWV, the high PP/normal baPWV, and high PP/baPWV groups were 1.66 (1.35 to 2.05), 1.09 (0.86 to 1.37), and 1.74 (1.43 to 2.13), respectively. Conclusions: High baPWV was independently associated with a higher risk of diabetes mellitus, and individuals with both high baPWV and high PP were at a still higher risk of diabetes mellitus.